PENGALAMAN RELIGIUS DALAM TAFSIR IBN ‘ARABI - Budiman, Ikhlas (Kanz Philosophia A Journal for Islamic Philosophy and Mysticism, 2016)
This paper discovered that religious experience was based on individual recognition of his Lord, called fitrah (QS. al-Aâ€™rÄf [7]: 172). The intensity of recognition of Lord, however, is different for anyone depending on their capacity. Religious experience of the believer is finding the guidance (QS. at TaghÄbun [64]: 11), while for the muttaqÄ« is receiving the FurqÄn (QS. al-AnfÄl [18]: 29). Religious experience of the mujÄhid is achieving the guidance to go through the paths (QS. al-â€˜AnkabÅ«t [29]: 69). The author researched the interpretation of the verses of religious experience particularly in Ibn ArabÄ«â€™s commentaries, Raá¸¥mah min al-Raá¸¥mÄn fÄ« TafsÄ«r wa IsyÄrÄt al-Qur`Än: Min KalÄm asy-Syaikh al-Akbar Muá¸¥y ad-DÄ«n Ibn al-â€˜ArabÄ« and al-FutÅ«á¸¥Ät al-Makkiyyah. This article analysis 4 verses of Qurâ€™an which has correlation with the discussion of religious experience. Through this work, it is clear that the religious experience is consequence of the primordial covenant between human and the Lord.